Effect of mitogen lectin on lymphocyte or brain cortex cell activation - Kovaru, Hana; Kovaru, Frantisek; Pav, Marek; Dvorak, Rudolf; Palikova, Miloslava; Raboch, Jiri; Zidková, Jarmila (Neuro endocrinology letters, 2010)
OBJECTIVES: We studied a) mitogen lectin (PHA) evoked changes of Na+/K+-ATPase activity in functionally different lymphocytes or brain cortex cells and b) quantitative relationship between PHA- evoked early enzyme activation and late lymphocyte proliferation were analyzed. MATERIALS AND METHODS: We performed biochemical analyses of Pi released from ATP by Na+/K+-ATPase activity. Lymphocyte proliferation was assayed by 3H-thymidine incorporation. RESULTS: We demonstrated PHA stimulated Na+/K+-ATPase activity of mouse spleen lymphocytes or freshly isolated brain cortex cells. Besides this, we estimated high stimulation of Na+/K+-ATPase activity and subsequent late 3H-thymidine incorporation into pig lymphocytes as both PHA dose and K+ ion concentration dependent. CONCLUSIONS: Thus, early PHA dose-dependent stimulation of Na+/K+-ATPase activity is a more general response in different animal species and functionally different cells. We measured both cell type- and PHA-dose dependent enzyme activity stimulation. We can suggest that intensity of early PHA induced Na+/K+-ATPase activation could be in relationship to subsequent elevated level of T lymphocyte proliferation. The Na+/K+-ATPase can be a part of mitogen lectin evoked signal transduction mechanisms.
Keywords: Animals; draslík; Sodium-Potassium-Exchanging ATPase; Mitogens; slezina; Potassium; Lymphocyte Activation; aktivace lymfocytů; mitogeny; Mice; fytohemaglutininy; prasata; T-lymfocyty; myši; Thymus Gland; Male; Mice, Inbred CBA; Swine; thymus; Spleen; Phytohemagglutinins; mozková kůra; Cerebral Cortex; buněčné kultury; T-Lymphocytes; mužské pohlaví; zvířata; myši inbrední CBA; Cell Culture Techniques; sodíko-draslíková ATPasa